PEMANFAATAN SAMPAH ORGANIK DAN AN-ORGANIK DI DESA SEDAYU KECAMATAN MUNTILAN - Nurul Dzakiya; Desi Kiswiranti; Radhitya Adzan Hidayah; Muchlis Muchlis (DHARMA BAKTI, 2019)
Banaran Village, Magelang District, is one of the villages producing stone crafts thathave high selling power such as mortar, pots and statues. However, waste rock fragmentsare a lot of problems for residents. In other hand, organic and non-organic waste that isaround the residents environment is also another problem that needs to be sought asolution. So that people need to be given insights about other functions of the rubbish,namely by utilizing it into stone temple crafts, planting media, organic fertilizer and fuel.The method of implementation is carried out with socialization to the community andtraining. As a result of this dedication, the residents of Sedayu are able to make wasteproducts into other products in accordance with the waste that is owned around theirrespective neighborhoods